Feminism Perspective in Economic Welfare of Women Traders at Sukawati Art Market, Gianyar - Luh Indrayani; Ni Wayan Ayu Santi; I Nyoman Sujana (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2023)
This study aims to determine the perspective of feminism in the economic welfare of women traders in the Sukawati Art Market, Gianyar. Economic welfare as seen from the use of income to meet needs. This type of research is a qualitative phenomenological approach to understand the essence of the experience of informants related to the phenomena experienced by women traders. As many as 8 informants explained things related to the economic welfare achieved by these women. The findings show that women traders have various reasons for running a business and maintaining a business that supports various needs. Women traders are also able to manage their income as traders in meeting health, education, consumption patterns, housing and social needs.